Production of a melt-formed inorganic ionically conductive electrolyte

CN116997534BActive Publication Date: 2026-11-03THERMAL CERAMICS UK
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202280022245.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-17
Filing Date
2022-03-16
Publication Date
2026-11-03
Estimated Expiration
2042-03-16

AI Technical Summary

Technical Problem

现有技术在生产石榴石或类石榴石固体锂离子导体时,存在生产方法复杂且成本高的问题,难以实现大规模生产。

Method used

The melt forming method is used to melt and shape the raw materials in a melting container, and then quickly quench them to form lithium-ion conductive products. By controlling the cooling rate and forming method, subsequent crushing steps can be reduced or eliminated, and amorphous or crystalline phase materials with the target particle size distribution can be obtained directly.

Benefits of technology

This technology enables large-scale production of high lithium-ion conductivity materials with lower energy and time, simplifying the processing flow, reducing costs, and improving the uniformity and ionic conductivity of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116997534B_ABST
    Figure CN116997534B_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing lithium ion conductive shaped particles or precursors thereof, the method comprising the steps of: A. feeding a mixture of raw materials into a melting vessel; B. melting the raw materials in the melting vessel to form a molten material; C. shaping the molten material; and D. quenching the molten material to produce the particles, wherein the cooling rate of the molten material is sufficient to form a plurality of glass or glass-ceramic particles, and wherein the molten material is shaped prior to quenching by a fluid cooling medium or simultaneously with quenching by a fluid cooling medium; and wherein the particles are formed by fluid impact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the production of melt-formed inorganic ionic conductive conductors for use, particularly as electrolytes or electrode materials, in energy storage devices. Background Technology

[0002] In recent years, with the development of battery technology towards higher energy density solutions, the development of solid lithium conductors has attracted widespread attention. Garnet or garnet-like solid lithium-ion conductors have become particularly promising candidate materials due to their excellent conductivity and wide electrochemical stability window.

[0003] US 8,658,317 discloses a garnet-like cubic crystal structure with a stoichiometric composition L 7+x A x G 3- x Zr2O 12 ,in

[0004] o L is independently a monovalent cation in each case. o A is independently a divalent cation in each case. o G is independently a trivalent cation in each case. o 0≤x≤3 and o O can be ionized by divalent or trivalent anions (such as N) 3- (to replace partially or completely)

[0005] L is particularly preferably an alkali metal ion, such as Li + Na + or K + In particular, various combinations of alkali metal ions are also possible for L. In a particularly preferred embodiment of the invention, L = Na + Sodium is very cheap and available in any quantity. Small Na... + Ions can move easily in garnet-like structures and combine with zirconium to produce chemically stable crystal structures.

[0006] A is any divalent cation or any combination of such cations. Divalent metal cations may preferably be used for A. Particularly preferred are alkaline earth metals such as Ca, Sr, Ba and / or Mg, as well as divalent transition metal cations such as Zn. It has been found that these ions move very little even when they do move in the garnet-like compounds according to the invention, such that ion conduction occurs substantially through L.

[0007] In the above composition, 0 ≤ x ≤ 2 is preferred, and particularly preferred is 0 ≤ x ≤ 1. In an embodiment according to the invention, x = 0, such that A is absent in the garnet-like compound.

[0008] G can be any trivalent cation or any combination of such cations. Trivalent metal cations can preferably be used for G. Particularly preferred is G=La.

[0009] A particularly preferred example of a compound according to the invention having a garnet structure is Li7La3Zr2O. 12 (LLZO). Li7La3Zr2O 12 Its high lithium-ion conductivity, good thermal and chemical stability in reaction with potential electrodes, environmental compatibility, availability of raw materials, low manufacturing cost, and simple production and sealing make it a promising solid electrolyte, particularly suitable for rechargeable lithium-ion batteries.

[0010] The ionic conductivity of these garnet-like materials is enhanced in cubic crystal form. Cubic crystal structures are thermodynamically stable at relatively high temperatures (e.g., > 600 °C), while tetragonal crystal structures are stable at room temperature. While the practicality of these garnet-like materials in energy storage devices and the like is undeniable, their adoption has been slowed, at least in part, due to the complex and expensive processing required to produce them.

[0011] Current production methods include: (i) the sol-gel process, in which a solution (aqueous or organic, typically acidic) is prepared using a soluble salt of the desired element. The prepared sol is then processed to produce the desired form (e.g., powder, fiber, sintered granules) and crystallized at high temperatures (typically > 1000°C) to obtain a preferred cubic crystalline phase. (ii) a mixed oxide process, in which a desired amount of oxide feedstock or precursor is ground together, followed by a calcination step to crystallize the powder into the desired cubic form. The grinding and calcination steps are typically repeated to achieve a homogeneous crystalline phase in the powder. Both of these production methods are expensive in terms of raw materials or processing costs due to their multi-step, batch synthesis nature.

[0012] Other methods, such as atomized spray pyrolysis, electrospinning, and thin film processing, either face scalability difficulties or low ionic conductivity.

[0013] US2019 / 0062176 addresses some of the issues associated with the need for repeated high-temperature heat treatment by using a molten salt reaction to form LLZO cubic crystalline powder.

[0014] US2019 / 0173130 discloses the production of Nb-doped LLZO by direct quenching or curing to form an intermediate amorphous composition, wherein the intermediate amorphous composition undergoes a pulverization process before being formed into sintered beads at 1150°C.

[0015] EP3439072 discloses a solid electrolyte comprising an amorphous phase on the surface of a lithium-ion inorganic conductive layer. The amorphous phase helps to reduce the interfacial resistance between the solid electrolyte and the electrode.

[0016] WO2020 / 223374 discloses the use of microwave plasma processing to form doped and undoped LLZO powders. While this technique claims to produce high-quality, high-purity stoichiometric LLZO, cost-effectively scaling up this technique and producing particle size distributions with a D50 greater than 50 nm remains a challenge.

[0017] While progress is being made in the development of solid electrolytes and their production methods, there is still room for further improvement in solid electrolytes and / or electrode materials that can be mass-produced. Summary of the Invention

[0018] In a first aspect of the invention, a method for producing molded lithium-ion conductive articles or precursors thereof is provided, comprising the following steps: A. Feed the mixture of raw materials into the melting container; B. Melt the raw materials to form a molten material; C. Shaping the molten material; and D. Quenching the molten material to produce the molded article. The cooling rate of the molten material is sufficient to form a molded article, wherein the forming of the molten material occurs before or at the same time as quenching. The molded article may be a sheet, film, granules, flakes, or fiber.

[0019] The melting vessel can be a furnace, and particularly an electric furnace, such as an electric arc furnace or an induction furnace. The furnace can be easily expanded from a kilogram capacity of 10 metric tons to a capacity of 100 metric tons or more.

[0020] The shaping of the molten material can occur from the flow of the molten material from the molten container through an outlet or nozzle (e.g., from a furnace). The shaping of the molten material flow further enhances the method's ability to maximize output. In one embodiment, the molten material flow impinged by a fluid cooling medium comprises multiple droplets.

[0021] In some embodiments, the method may include at least two melting vessels, one providing a molten flow for molding, while the other is in the process of melting the raw material into a molten material. Within this configuration, a nearly continuous flow of molten material can be supplied for molding, thereby maximizing the yield of the method.

[0022] The molding of the molten material (e.g., molten flow) can be achieved by impinging it with a fluid flow. The volume and velocity of the fluid flow can be adjusted to control the particle size distribution of the resulting solidified particles. The particles can be substantially spherical due to the influence of surface tension in their molten state. The resulting particle size distribution (PSD) preferably achieves a target PSD with minimal or no further pulverization steps. Minimal pulverization steps may include no more than one or two pulverization steps and / or a reduction in D50 of no more than 15 µm or 10 µm.

[0023] Alternatively, the molten material can be formed by guiding it through a nozzle to atomize it into particles. The atomization can be performed in an inert atmosphere. The atomized particles can be sprayed into a quenching medium, such as a quenching fluid and / or a quenching surface. Further details of this method are disclosed in US4781741, which is also disclosed herein by reference.

[0024] Preferably, the raw materials (including optional dopants) are selected to provide a composition capable of forming an ionically conductive crystalline phase or an ionically conductive semi-crystalline phase. The molded article may initially contain or consist of an amorphous phase, depending on the end-use application, and may be further transformed into an ionically conductive crystalline or semi-crystalline phase. Providing molded articles with defined shapes and morphologies that can be produced on a commercial scale (e.g., metric tons / day) will meet the growing demand in the energy storage device market. Advantageously, the method of the present invention enables the production of such molded articles with minimal or no grinding steps.

[0025] The composition of the molded article preferably contains a content of at least 1.0 x 10 at 30°C or room temperature. -6 S cm -1 Or at least 1.0 x 10 -5 S cm -1 A crystalline phase with high ionic conductivity (lithium ions) or an amorphous component that can be converted into an ionicly conductive crystalline phase (e.g., through heat treatment).

[0026] In one embodiment, the composition corresponds to a composition capable of forming a garnet or garnet-like crystalline phase (preferably a cubic crystalline phase) and / or an amorphous component capable of being transformed into a garnet-like crystalline phase (e.g., by heat treatment).

[0027] In another embodiment, the composition corresponds to the ability to form perovskites (e.g., lithium lanthanum titanium oxide-Li). 3x La 2 / 3xCompositions of TiO3 or perovskite-like crystalline phases and / or amorphous components capable of being converted into perovskite or perovskite-like crystalline phases (e.g., through heat treatment). In addition to being used as an electrolyte material, lithium lanthanum titanium oxide can be used as an electrode material.

[0028] In another embodiment, the composition corresponds to a spinel or spinel-like crystalline phase capable of forming (e.g., lithium titanate, such as Li4Ti5O). 12 The composition may be a combination of the crystalline phase or an amorphous component capable of being converted into the crystalline phase (e.g., by heat treatment). In addition to being used as an electrolyte material, the composition may be used as an electrode material (e.g., an anode material).

[0029] In some embodiments, the molded article is primarily (i.e., at least 50% by weight) amorphous. In some embodiments, the molded article has a primary amorphous phase and optionally a secondary crystalline phase. The molded article may be a glassy molded article or a glass-ceramic molded article. In other embodiments, the molded particles contain at least 20% by weight of an amorphous phase.

[0030] It has been found that by increasing the amorphous component of the molded article used for the formation of solid electrolytes, the resulting solid electrolyte exhibits improved ionic conductivity compared to using molded articles with a lower amorphous content. While not wishing to be limited by theory, it is believed that particles with a high amorphous content can be transformed into a crystalline state with fewer defects that suppress ionic conductivity, compared to particles with a low amorphous content and already possessing a significant crystalline structure. It has also been found that high amorphous particles can be transformed into the target cubic crystalline phase using lower temperatures and times compared to particles containing lower amorphous particles. Therefore, high amorphous particles can be processed with less energy and time, making them suitable for large-scale production. Advantageously, the high amorphous content particles can be transformed into the target morphology during the sintering of the molded article into a solid electrolyte (e.g., a membrane), rather than heat-treating the molded article to form the target morphology before sintering it into a solid electrolyte or electrode.

[0031] In some embodiments, the molded article has a core-shell structure. The ratio of core material to shell material can be controlled using a combination of particle size and composition with quenching conditions. The core can be crystalline or amorphous. The shell can be crystalline or amorphous. In one embodiment, the shell is primarily amorphous and the core is primarily crystalline. In some embodiments, the shell of the core-shell molded article has a higher ionic conductivity than the core. In embodiments where the core has a higher conductivity than the shell, the core-shell article can be ground to release particles of amorphous and crystalline material in a defined ratio.

[0032] The method may further include a step of separating the molded articles by size. For this purpose, air grading or screening techniques can be used. Because the morphology of the molded articles is affected by the quenching process, size grading of the separated article groups can result in groups of articles with more uniform morphology. This can be particularly advantageous when the articles are used as intermediates in forming the final product, where quality depends on the size and / or morphology of the intermediate material.

[0033] In one embodiment, the molded articles are categorized by size into a target particle size range and an oversized range. The oversized range can be reprocessed (e.g., remelted) or ground to the target particle size range. In some embodiments, the molded particles comprise a mixture of spherical (unground) particles and non-spherical (ground) particles. Preferably, the mixture contains at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 60% by weight, or at least 70% by weight, or at least 80% by weight of spherical articles (e.g., articles having a sphericity of at least 0.7). The mixture may contain at least 1% by weight, or at least 2% by weight, or at least 5% by weight of non-spherical particles.

[0034] In some embodiments, the average maximum distance between the central axis of the molded article and the nearest (outer) surface of the article is less than 10 mm (e.g., for a sphere with a diameter of less than 20 mm), or less than 5 mm, or less than 2 mm, or less than 1 mm, or less than 500 µm, or less than 250 µm, or less than 225 µm, or less than 200 µm, or less than 100 µm, or less than 50 µm, or less than 10 µm, or less than 5.0 µm, or less than 4.0 µm, or less than 3.0 µm, or less than 2.0 µm, or less than 1.0 µm, or less than 0.50 µm, or less than 0.20 µm. The smaller the maximum distance, the higher the cooling rate at the core of the particle and the more uniform the particle morphology.

[0035] Because the molded articles are preferably melt-derived, they are preferably glassy or glassy in nature. The glassy / glassy molded articles (i) can be intermediates in processes to be converted into different morphological forms; or (ii) can be used as components within composite electrolytes (e.g., polymer composite electrolytes). While glassy electrolytes are generally considered to have lower ionic conductivity than their crystalline counterparts, amorphous molded articles have the advantages of: (i) being easier to manufacture on a large scale; and (ii) being easier to convert into the desired crystalline phase (if desired).

[0036] The molded article may have the following stoichiometric composition: Formula 1: L 7+w-3x-z M 1 w M 2 xG 3-w Zr 2-y-z M 3 y M 4 z O 12 ,in o L is independently a monovalent cation in each case. o G is independently a trivalent cation in each case. o M 1 = Divalent dopant, o M 2 = Trivalent dopant o M 3 = Tetravalent dopant o M 4 = Pentavalent dopant ow, x, y, and z are each in the range from 0 to < 1.0. o O can be ionized by divalent or trivalent anions (such as N) 3- (to replace partially or completely)

[0037] In other embodiments, the ion-conductive molded article may be represented by Formula 2 or 3.

[0038] Formula 2 Li 7-x M 1 x La 3-a M 2 a Zr 2-b M 3 b O 12

[0039] Formula 3 Li 7-x La 3-a M 2 a Zr 2-b M 3 b O 12

[0040] In Equation 1, M 1 Including at least one of gallium (Ga) and aluminum (Al), in formulas 2 and 3, M 2 Including at least one of calcium (Ca), strontium (Sr), cesium (Cs), and barium (Ba), M 3 It includes at least one of aluminum (Al), tungsten (W), niobium (Nb) and tantalum (Ta), and 0 ≤ x < 3, 0 ≤ a ≤ 3 and 0 ≤ b < 2.

[0041] In Equation 1, x can be 0.01 to 2.1, for example 0.01 to 0.99, for example 0.1 to 0.9, and 0.2 to 0.8. In Equation 1, a can be 0.1 to 2.8, for example 0.5 to 2.75, and b can be 0.1 to 1, for example 0.25 to 0.5.

[0042] In the compound represented by Equation 2, the dopant can be M. 1 M 2 and M 3 At least one of them. In the compound represented by Formula 3, the dopant can be M. 2 and M 3 At least one of them.

[0043] The ion-conductive molded article may be a derived metal sulfide glass, metal phosphate glass (e.g., LiTi2(PO4)3), metal borate glass, and / or metal silicate glass. The metal may include metals corresponding to the chemistry of metal-ion batteries and includes magnesium, sodium, aluminum, or lithium.

[0044] The ion-conductive molded article composition is preferably a composition that forms a crystalline phase or a predominant crystalline phase without quenching the molten material.

[0045] In some implementations, the sulfur-based glass is Li2S-YS n Li2S-YS n -YO n Types and combinations thereof, wherein Y is selected from the group consisting of Ge, Si, As, B, or P, and n = 2, 3 / 2, or 5 / 2, and the glass is chemically and electrochemically compatible with lithium metal contact. Suitable glasses may contain one or more glass-forming agents selected from the group consisting of P2S5, P2O5, SiS2, SiO2, B2S3, and B2O3 as glass modifiers. In some embodiments, the glass may be phosphorus-free.

[0046] In some embodiments, the primary glass forming agent is SiO2 (i.e., the largest glass forming component is SiO2). In some embodiments, the primary glass forming agent is SiS2.

[0047] In some implementations, no further heat treatment step is required after the quenching step to transform the morphological form (e.g., amorphous and / or crystalline form).

[0048] Regardless of the specified valence of the dopant, the stoichiometric composition covers all dopants with all valence states. Specifically, the dopant can be selected from the group consisting of: Al, Ga, Ta, Nb, Zn, Mg, Sb, W, Mo, Rb, Sc, Ca, Sn, Bi, Ba, Sr, Zn, In, Y, Si, Ge, and Ce. For multivalent dopants, such as Mo with a specified 4+ valence state, the dopant can also exist in another valence state (e.g., Mo 6+). The dopant can include one or more dopants having the same or different valence states.

[0049] Therefore, the stoichiometric composition can be alternatively expressed by Equation 4: L q1 D q4 G q2 Zr q3 O 12 ,in o L is independently a monovalent cation in each case. o G is independently a trivalent cation in each case. oD = is a dopant. o q1 is preferably in the range of 0 to 8 or higher. o q2 is preferably in the range of 0 to 3 o q3 is preferably in the range of 0 to 2. o q4 is preferably in the range of 0 to 1 o O can be ionized by divalent or trivalent anions (such as N) 3- Partial or complete replacement, L is preferably selected from the group consisting of Li, Na, and K. In a preferred embodiment, L is Li. G is preferably La.

[0050] It has been unexpectedly discovered that, with L 7+w-3x-z M 1 w M 2 x G 3-w Zr 2-y-z M 3 y M 4 z O 12 Quenching of molten materials with a stoichiometric composition can produce molded articles containing an amorphous phase, which can be transformed into L during a densification process (preferably for film formation). 7+w-3x-z M 1 w M 2 x G 3-w Zr 2-y-z M3 y M 4 z O 12 The densification process can be carried out at high temperatures (e.g., at least 900°C, at least 1000°C, or at least 1100°C) and optionally under pressure. It has been found that densifying a layer of molded article into a film can also transform a predominantly amorphous molded article into a predominantly crystalline film.

[0051] The use of predominantly amorphous particles can also contribute to achieving high membrane density. The relative density of the membrane may be at least 90%, at least 92%, at least 94%, at least 96%, at least 97%, or at least 98%. In some embodiments, a residual amorphous content is retained. It is believed that the residual amorphous content reduces interfacial resistance, thereby enhancing the ionic conductivity of the membrane relative to membranes formed through densification of the predominantly crystalline article.

[0052] In one embodiment, the molded article comprises L 7+w-3x-z M 1 w M 2 x G 3-w Zr 2-y-z M 3 y M 4 z O 12 The main amorphous phase and the minor cubic crystalline phase.

[0053] In one embodiment, the molded article is a film. The film can be between about 5 µm and 500 µm. The method for forming the film may further include the following steps: E. Form the molded article into a layer; F. Heat-treating the layer to densify the layer; and G. The heat treatment is carried out for a sufficient time to achieve the target morphology.

[0054] The membrane can also be formed under pressure to facilitate the densification process and control the resulting morphology.

[0055] Heat treatment conditions can vary depending on the composition and morphology of the film. Guidelines for suitable heat treatment or sintering conditions can be found in Table 2.1 of the following literature: Ramakumar et al., “Lithium garnets: Synthesis, structure, Li + conductivity, Li +"Dynamics and applications"; Progress in Material Science 88 (2017) 325-411, which is incorporated herein by reference.

[0056] In some embodiments, the molded article does not require any further destructive particle size reduction processes (e.g., ball milling), but can be obtained using screening or separation steps to achieve the desired particle size fraction. Reducing or eliminating additional size reduction steps further simplifies the process. In embodiments that do involve size reduction steps, the size reduction factor (unground D50 particle size / ground D50 particle size) is preferably less than 100, less than 50, less than 25, less than 10, or less than 5. The size reduction step (e.g., grinding) can be performed immediately after the quenching step (i.e., before any heat treatment step).

[0057] The molded article can be formed into a layer using a volatile solvent as a carrier via a casting process. In one embodiment, the molded article is formed using a solvent-soluble inorganic binder solution, such as a lithium silicate solution.

[0058] In some embodiments, the formed article is a lamellar crystal. Lamellar crystals are advantageous for obtaining a uniform quenching rate and thus a uniform morphology. The use of lamellar crystals can also lead to a reduction in the interfacial area between the particles in the film precursor layer, thereby resulting in a lower interfacial resistance within the film. The lamellar crystals can have an average thickness between 50 nm and 100 µm; and the aspect ratio of the minimum and maximum lateral dimensions to the thickness is each between 10:1 and 25,000:1.

[0059] In some implementations, the aspect ratios of the minimum and maximum lateral dimensions to the thickness are each in the range of 110:1 to 25,000:1.

[0060] In some implementations, the aspect ratios of the minimum and maximum lateral dimensions to the thickness are each in the range of 200:1 to 25,000:1.

[0061] The lamellar crystal may have an average thickness between 50 nm and 1.0 µm. The lamellar crystal may contain a minimum and maximum lateral dimension of at least 40 µm. In some embodiments, the maximum lateral dimension of the lamellar crystal may be at least 45 µm.

[0062] In some implementations, a further heat treatment step is employed to transform the predominant amorphous LLZO phase into the predominant cubic LLZO phase.

[0063] In some implementations, non-stoichiometric amounts of feedstock components are used to form non-stoichiometric melts that facilitate the formation of amorphous phases. A non-stoichiometric melt is defined as a melt with components having a stoichiometric composition, but whose stoichiometric amounts do not satisfy the requirements for a crystalline melt.

[0064] This simplified processing route contrasts with the complex, multi-step methods of existing technologies, which involve forming a cubic phase through a solid-state conversion mechanism, requiring multiple steps and extended time periods at high temperatures.

[0065] Dopants can be used to stabilize preferred crystalline phases or alternatively act as crystallization inhibitors to facilitate the formation of molded articles with high amorphous content.

[0066] In some embodiments, the molded article comprises at least 60% by weight, or at least 70% by weight, or at least 80% by weight, or at least 90% by weight, or at least 95% by weight, or at least 98% by weight. In some embodiments, the molded article comprises no more than 98% by weight, or no more than 90% by weight, or no more than 80% by weight. The molded article may contain less than 50% by weight, or less than 40% by weight, or less than 30% by weight, or less than 20% by weight, or less than 10% by weight of material having a first crystalline form (e.g., a cubic garnet-like crystal). The molded article may contain less than 30% by weight, or less than 20% by weight, or less than 10% by weight, or less than 5% by weight of material in a second crystalline form (e.g., a tetragonal garnet-like crystal). The amount of the first crystalline form is preferably greater than that of the second crystalline form. In a preferred embodiment, the second crystalline form is not detected by XRD. The molded article may contain more than 0% by weight or at least 5% by weight or at least 10% by weight or at least 15% by weight or at least 20% by weight of crystalline material or at least 25% by weight of crystalline material or at least 30% by weight of crystalline material.

[0067] Molded articles can contain amorphous or glassy surfaces. Although the ionic conductivity of the crystalline phase can be high, the advantage of the large-scale manufacturability of predominantly amorphous molded articles is sufficient to offset any reduction in ionic conductivity. Furthermore, the formation of the amorphous phase helps to reduce the interfacial resistance of the ionic conductivity.

[0068] Preferably, the raw material is melted to a temperature sufficient to melt it above the melting temperature of the target composition and its crystalline form (i.e., the cubic crystal form of the garnet-like material). The melting vessel can operate at or above 800°C, or at least 900°C, or at least 1000°C, or at least 1100°C, or at least 1200°C, or at least 1300°C, or at least 1400°C. The maximum operating temperature may be limited by the temperature at which the composition decomposes (e.g., decomposes into La₂Zr₂O₇ and Li₂ZrO₃).

[0069] Preferably, a cooling medium is used to quench the molten material. The cooling medium may be a fluid (gas or liquid) flow and / or a moving object (e.g., a rotating wheel or roller).

[0070] The average quenching rate between the contact of the molten material with the cooling medium and the solidification of the molten material is at least 50°C / second or at least 100°C / second or at least 200°C / second or at least 400°C / second or at least 500°C / second or at least 600°C / second or at least 800°C / second or at least 1000°C / second or at least 1500°C / second or at least 2000°C / second or at least 4000°C / second or at least 6000°C / second or at least 10,000°C / second.

[0071] In one embodiment, when the molten material comes into contact with the cooling medium, the average temperature difference between the molten material and the cooling medium is at least 200°C, at least 300°C, at least 400°C, at least 500°C, at least 600°C, or at least 700°C.

[0072] Preferably, the molten material is shaped prior to quenching. By shaping the molten material, the maximum distance between the central axis of the particles and the particle surface can be controlled to achieve rapid cooling of most or all of the shaped material. Furthermore, by shaping the molten material to a size suitable for end-use applications (e.g., electrode systems in batteries) with minimal additional processing to reduce its size, there is no tendency for the crystalline phase to change from a preferred cubic form during size-reduction operations (such as grinding or milling). Further contamination of the material can also be avoided by minimizing additional processing steps.

[0073] However, when further size reduction is required, the method may include grinding and polishing steps. These additional size reduction steps may be carried out in an inert fluid (gas or liquid, e.g., water or anhydrous organic solvent) to avoid surface contamination or the formation of contaminants.

[0074] The method may further include a washing step or a surface treatment step to remove contaminants from the surface and / or treat the surface to enhance surface properties (i.e., functionalize or modify the surface morphology (e.g., surface area or porosity) to achieve, for example, improved contact with the polymer when the molded article is part of a polymer composite).

[0075] Quenching relies on a rapid decrease in the temperature of the molten material to cause solidification, leaving no time for the crystalline structure to rearrange into a more thermodynamically stable structure at the quenching temperature. It should be understood that many factors will affect the quenching process that achieves this effect, including but not limited to: The shape of the molten material; The temperature of the molten material and the cooling medium used for quenching the molten material; Surface area to volume ratio of molten material The maximum distance between the central axis of the molten material and its surface; The heat capacity and electrical conductivity of the molten material and the cooling medium; and The volume of the cooling medium and its movement relative to the molten material The molding material may include particles (having various shapes, including spherical or near-spherical), films, or fibers. In embodiments where the particles are spherical or near-spherical, the sphericity coefficient of the particles may be at least 0.6, at least 0.7, at least 0.8, or at least 0.9. Sphericity is defined as the ratio of the surface area of ​​a sphere of equal volume to the surface area of ​​a particle: (π 1 / 3 (6V p ) 2 / 3 / A p ) Where V p Represents the volume of the particle and A p This indicates its surface area.

[0076] Spherical particles can be formed by avoiding additional grinding steps in the initial shaping of molten material. Spherical particles offer the advantage of providing uniform processing characteristics, which minimizes internal stresses during heating and cooling operations, such as film formation. Compared to spherical particles formed directly from molten material, milled particles tend to have a greater degree of geometric irregularity and a higher specific surface area.

[0077] In some embodiments, the molded article may include one or more shapes (e.g., lamellar crystals and granules); include one or more compositions and / or include one or more crystalline structures.

[0078] Due to variations in the size of the molding material, in order to obtain the desired level of amorphous or crystalline structure (e.g., cubic LLZO), it may be necessary to separate the molding material based on size or shape to isolate the material with a predominantly cubic crystal structure. Separation techniques may include sieving, air classification, etc.

[0079] In some implementations, the combination of cooling rate and particle size is sufficient to form L 7+x A x G 3-x Zr2O 12 The main amorphous forms, such as doped lithium lanthanum zirconium oxide.

[0080] In some embodiments, the molded article has an average maximum cross-sectional dimension of less than 50 mm, less than 20 mm, less than 10 mm, less than 1 mm, less than 500 µm, less than 250 µm, less than 100 µm, less than 50 µm, less than 10 µm, less than 5.0 µm, less than 4.0 µm, less than 3.0 µm, less than 2.0 µm, or less than 1.0 µm. The average minimum cross-sectional dimension may be 50 nm or more, 100 nm or more, 200 nm or more, or 500 nm or more. In other embodiments where the molded article comprises a film or sheet, the maximum cross-sectional dimension may be in the range of 100 mm to 1.0 μm.

[0081] In some implementation schemes (including) Figure 2 Among those shown, some particles have diameters of about 2 µm and about 3 µm and about 4 µm and about 5 µm at the smaller end of the range. At the larger end of the range, some particles may have diameters of about 20 µm and about 30 µm and about 40 µm. In some embodiments, the particles have diameters ranging from 3 µm to 40 µm, or 4 µm to 30 µm, or 5 µm to 20 µm.

[0082] In some embodiments, the particle size distribution has an average or median (D50) particle size greater than 600 nm or greater than 700 nm or greater than 800 nm or greater than 900 nm or greater than 1.0 µm or greater than 1.1 µm or greater than 1.2 µm or greater than 1.3 µm or greater than 1.4 µm or greater than 1.5 µm or greater than 1.6 µm or greater than 1.7 µm or greater than 1.8 µm or greater than 1.9 µm or greater than 2.0 µm or greater than 2.5 µm or greater than 3.0 µm or greater than 3.5 µm or greater than 4.0 µm or greater than 4.5 µm or greater than 5.0 µm or greater than 6.0 µm or greater than 7.0 µm. In some embodiments, the particle size distribution has an average value or D50 of less than 500 µm or less than 450 µm or less than 400 µm or less than 300 µm or less than 200 µm or less than 150 µm or less than 120 µm or less than 100 µm or less than 80 µm or less than 60 µm or less than 50 µm or less than 40 µm or less than 30 µm or less than 20 µm or less than 18 µm or less than 16 µm or less than 14 µm or less than 12 µm or less than 10 µm or less than 8.0 µm or less than 6.0 µm or less than 4.0 µm or less than 2.0 µm or less than 1.0 µm. D10 may be greater than or equal to D50 / 4. D90 may be less than or equal to D50. 4.

[0083] In a preferred embodiment, the average value or D50 of the shaped particles is in the range of 600 nm to 20 µm, and preferably in the range of 600 nm to 10 µm. Particles in this range may require little or no pulverization steps (e.g., one or two steps) before being converted into a solid electrolyte.

[0084] In another embodiment, the average value or D50 of the molded particles is in the range of 600 nm to 2.0 µm. Particles in this range may not require further pulverization before being converted into a solid electrolyte.

[0085] In a preferred embodiment, the molten material is simultaneously quenched and shaped. This can be achieved by impinging the molten material with a cooling medium to reduce the size of the shaped molten material and provide rapid cooling, resulting in the solidified shaped material. In another embodiment, the shaping process occurs at a high temperature (e.g., greater than 900°C, 1000°C, 1200°C, 1300°C, or 1400°C), wherein the shaped material is still in molten form. Higher shaping temperatures favor the formation of smaller shaped materials because the viscosity of the molten liquid material is lower at higher temperatures.

[0086] Doped lithium lanthanum zirconium oxide is preferably represented by one of the following formulas: Formula 5: Li 7+w La 3-w M 1 w Zr2O 12 Where 0 < w < 0.6 or < 1.0, and M 1 = Divalent dopants, such as Ca, Sr, Ba Formula 6: Li 7-3x M 2 x La3Zr2O 12 Where 0 < x < 0.6 or < 1.0, and M 2 = Trivalent dopants, such as Al and Ga Formula 7: Li7La3Zr 2-y M 3 y O 12 Where 0 < y < 0.6 or < 1.0, and M 3 = Tetravalent dopants, such as Mo, Ce, W Formula 8: Li 7-z La3Zr 2-z M 4 z O 12 Where 0 < z < 0.6 or < 1.0, and M 4 = Pentavalent dopants, such as Ta In some embodiments, the stoichiometric composition comprises or consists of the following: lithium lanthanum zirconium oxide (Li7La3Zr2O) 12 , where w+x+y+z = 0). In some embodiments, the stoichiometric composition comprises or consists of the following: doped lithium lanthanum zirconium oxide (w+x+y+z > 0).

[0087] The dopant level is preferably sufficient to stabilize the cubic crystalline phase. The dopant level can vary, but typically ensures that 0 < w+x+y+z < or 2.0 or 0.05 < w+x+y+z < 1.0 or 0.1 < w+x+y+z < 0.8 or 0.2 < w+x+y+z < 0.6. A dopant level of at least 0.05, at least 0.1, or at least 0.2 may be required to stabilize the cubic crystal structure during the quenching process. In some embodiments, w = 0.

[0088] The dopant is preferably selected from the group consisting of: Al, Ga, Ta, Nb, Zn, Mg, Sb, W, Mo, Rb, Sc, Ca, Sn, Bi, Ba, Sr, Zn, In, Y, Si, Ge and Ce.

[0089] In one embodiment, the dopant includes Al and / or Mo.

[0090] Preferably, w, x, y and / or z are greater than 0.02 or greater than 0.05 or greater than 0.1 or greater than 0.2 or greater than 0.3.

[0091] In one embodiment, x is in the range of 0.1 to 1.0, 0.2 to 0.8, or 0.3 to 0.6. In one embodiment, M 2 = Al. In another embodiment, dopant M 4 Includes or is composed of Ta.

[0092] In one embodiment, the dopant is provided to the molten vessel via a sacrificial electrode, such as in an electric arc furnace. The electrodes used in the furnace are susceptible to corrosion in the operating environment.

[0093] The amount of dopant derived from the sacrificial electrode can be controlled by one or more of the following: a. The temperature of the molten container; b. Distance between electrode tips c. Electrode settings (voltage and amperes) d. Exposure of the sacrificial electrode to an oxygen-containing environment; e. The surface area of ​​the sacrificial electrode in contact with the molten material; f. Composition of the sacrificial electrode; g. Composition of the molten material; and h. Residence time in the molten container In some embodiments, the dopant provided via the sacrificial electrode is Mo and / or W. In some embodiments, the dopant is provided in part from the sacrificial electrode, and the remaining dopant may be added as part of the raw material mixture.

[0094] In an alternative implementation, the dopant is entirely derived from the raw materials.

[0095] In a second aspect of this disclosure, a product is provided that is produced (obtained or available) by means of the method according to the first aspect of this disclosure.

[0096] In one embodiment, the article forms part of a polymeric composite electrolyte comprising a polymer and the article. The composite electrolyte may be contained in the range of 2% to 98% by weight, or in the range of 5% to 60% by weight, or at least 10% to 40% by weight of the article. Suitable polymers include, but are not limited to, polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyimide (PI), polyvinylpyrrolidone (PVP), polyethylene oxide (PEO), polyvinyl alcohol (PVA), polylactic acid (PLA), polysaccharides (e.g., carboxymethyl cellulose (CMC)), styrene-butadiene rubber (SBR), and their derivatives and combinations.

[0097] The article can have a particle size of at least 1.0 x 10 at 30°C or room temperature. -6 S cm -1 Or 5.0 x 10 -6 S cm -1 Or 6.0 x 10 -6 S cm -1 Or 7.0 x 10 -6 S cm -1 Or 8.0 x 10 -6 S cm -1 Or 9.0 x 10 -6 S cm -1 Or 1.0 x 10 -5 S cm -1 Or 1.2 x 10 -5 S cm -1 Or 1.4 x 10 -5 S cm -1 Or 1.5 x 10 -5 S cm -1 Or 2.0 x 10 -5 Scm -1, Or 3.0 x 10 -5 S cm -1 Or 4.0 x 10 -5 S cm -1 Or 5 x 10 -5 S cm -1, Or 1 x 10 -4 S cm -1 Or 5.0 x 10 -4 S cm -1 Or 1.0 x 10 -3S cm -1 The ionic conductivity (grain or total).

[0098] Grain conductivity of the material (σ) g It is related to the ionic conductivity through a single grain or microcrystal and depends on a variety of factors, including but not limited to composition, crystallinity and temperature.

[0099] In a third aspect of the invention, a molded article (preferably glassy) comprising an ionicly conductive composition is provided, wherein the average maximum distance between the central axis of the molded article and the nearest surface is not greater than 10.0 mm (or not greater than 250 µm and greater than 600 nm), and wherein the molded article comprises at least 50 wt%, at least 60 wt%, or at least 70 wt% of an amorphous phase.

[0100] In a variation thereof, glassy particles comprising a garnet-like, perovskite-like, or spinel-like composition are provided, wherein the particle size D50 is in the range of 600 nm (or 800 nm or 1000 nm) to 20 µm; the sphericity is 0.7 or greater; and the particles contain at least 50% by weight of an amorphous phase.

[0101] Particles within this size range are particularly suitable for forming solid electrolytes, including membranes used in energy storage devices such as lithium-ion batteries. Larger particles require additional pulverization steps to achieve the target PSD. Furthermore, to obtain a higher amorphous content, a greater quenching process is needed in terms of quenching medium temperature and / or heat capacity. However, smaller particles are more difficult to manipulate and process on a large scale.

[0102] The average maximum distance between the central axis of the molded article and the nearest surface may be no greater than 5.0 mm, 1.0 mm, 500 µm, 450 µm, 400 µm, 350 µm, 300 µm, 250 µm, 225 µm, 200 µm, 150 µm, 100 µm, 90 µm, 80 µm, 70 µm, 60 µm, 50 µm, 40 µm, 30 µm, 25 µm, 20 µm, 15 µm, 10 µm, 9.0 µm, 7.0 µm, 5.0 µm, 4.0 µm, 3.0 µm, or 2.0 µm. The greater the distance between the central axis and the nearest surface, the greater the energy required to extract from the particles to quench them within a sufficient time to maintain the preferred amorphous content, e.g., at least 50% by weight of amorphous material. The balance between scalability, cost, and the required level of amorphous material will influence the selection parameters for a given application.

[0103] The ionicly conductive composition is preferably a composition that forms garnet-like crystals, a composition that forms perovskite-like crystals, or a composition that forms spinel-like crystals.

[0104] The molded article may include the technical features previously described in the first aspect of the invention.

[0105] In a fourth aspect of the invention, an ion-conductive film intermediate comprising a molded article layer of the third aspect of the invention is provided.

[0106] The layer may be a precursor to the entire membrane or one of multiple layers within the membrane. In one embodiment, the layer is located on one of the outer layers of the membrane. In another embodiment, the layer is located on each outer layer of the membrane. The intermediate layer may contain or consist substantially of a crystalline phase. In some embodiments, the intermediate layer contains or consists of a cubic garnet crystalline phase.

[0107] In a fifth aspect of the invention, the use of the molded article of the third aspect for the manufacture of solid electrolytes is provided.

[0108] In a sixth aspect of the invention, a composite material comprising a solvent-soluble inorganic binder matrix is ​​provided, the solvent-soluble inorganic binder matrix comprising: Solvent-soluble inorganic adhesives; and Multiple ionic conductive particles; The amount of the ionicly conductive particles is in the range of 20% to 99.5% by weight, based on the total weight of the ionicly conductive particles and the solvent-soluble inorganic binder.

[0109] The ionicly conductive particles can be crystalline, semi-crystalline, or amorphous.

[0110] Solvent-soluble inorganic binders can be used to form films containing solvents, which are removed after film formation (e.g., by drying / sintering). In some embodiments, the inorganic binder is a water-soluble inorganic binder. The water-soluble inorganic binder can be water glass (e.g., sodium, potassium, or lithium silicate). In a preferred embodiment, the water-soluble inorganic binder is lithium silicate. The use of the water-soluble binder can be a means of densifying the film at lower temperatures and shorter sintering times.

[0111] In some embodiments, the membrane comprises the inorganic adhesive in the range of 1% to 40% by weight; or 2% to 20% by weight; or 3% to 10% by weight.

[0112] Unless the context clearly indicates otherwise, references to LLZO should be understood to include doped LLZO.

[0113] References to glassy molded articles (e.g., granules) should be understood to include references to glassy or glass-ceramic or melt-formed molded articles.

[0114] The reference to ionic conductivity phases means having a conductivity of at least 1.0 x 10⁻⁶ at 30°C or room temperature. -6 S cm -1 Or at least 1.0 x 10 -5 S cm -1 The phase of ionic conductivity.

[0115] A reference to the major phase is a reference to the phase that accounts for the highest proportion (by weight) of the composition.

[0116] For the purposes of this invention, garnet-like phases encompass both garnet-like crystalline phases and amorphous phases capable of transforming into garnet-like crystalline phases.

[0117] The nearest surface relative to the central axis is preferably perpendicular to the central axis. The measurement is preferably taken from the periphery of the article.

[0118] For the purposes of this invention, it primarily means at least 50% by weight.

[0119] Compositions forming garnet-like crystals (or garnet-like structures) are defined as compositions corresponding to or approximating the stoichiometric composition of garnet or garnet-like crystals (such as cubic LLZO structures or their doped variants). Representative garnet-like compositions are provided in Formulas 1-8.

[0120] The (perovskite-like) composition that forms perovskite-like crystals is defined as corresponding to or approximating perovskite (e.g., Li). 3x La 2 / 3x The stoichiometric composition of TiO3 or perovskite-like crystals (such as LLTO crystal structures or their doped variants) including lithium-rich (e.g., La) 0.5 Li O.5 TiO3) or lithium-poor (e.g., La) 0.56 Li O.33 A composition of TiO3 (stoichiometry).

[0121] Compositions that form spinel crystals (or spinel-like compositions) are defined as those corresponding to or approximating spinel (e.g., Li4Ti5O). 12 A composition of stoichiometric composition of spinel-like crystals (including their doped variants).

[0122] For the purposes of this invention, water- or solvent-soluble inorganic adhesives will include inorganic adhesives that are soluble in water at room temperature or form colloidal solutions at room temperature.

[0123] For clarity, the surface closest to the central axis of the workpiece is the closest outer surface.

[0124] For the purposes of this invention, the central axis of the article is a central axis extending parallel to the longest 2D plane of the article. Therefore, the distance between the central axis and the nearest surface corresponds to the distance between the quenching medium and the central axis. This parameter will affect the time required to quench the material along the central axis.

[0125] D50 is the size of the fractional distribution in micrometers, where half of the particles are above this diameter and half are below it. Unless otherwise noted, D50 is calculated using laser diffraction techniques with Malvern Panalytical Morphologi4, version 10.32 software running Morpholigi ID. The sphericity of the particles is also determined using this instrument. A sample volume of approximately 20 mg is used.

[0126] The average particle size can be calculated from a sample population of at least 20, preferably at least 50, at least 100, or at least 500 particles. Scandium can be used. TM 5.1 Use software to determine granularity.

[0127] Screening particle size refers to the particle size classification corresponding to the size of the sieve through which the particles are suitable after screening. The 40 µm-180 µm screening particle size corresponds to particles that are suitable to pass through a 180 µm sieve but not suitable to pass through a 40 µm sieve. Attached Figure Description

[0128] Figure 1 This is a schematic diagram of an apparatus for producing molded articles according to the method of this disclosure.

[0129] Figure 2 Is using Figure 1 SEM images of molded products prepared by the equipment.

[0130] Figure 3 Is using Figure 1 SEM images of core-shell molded products prepared by the equipment.

[0131] Figure 4 Is using Figure 1 XRD diffraction patterns of the size group of molded products prepared by the equipment.

[0132] Figure 5 It is made by sintering Figure 2 XRD diffraction pattern of the film formed from the molded product.

[0133] Figure 6 These are SEM images of sample 1703 from Table 1.

[0134] Figure 7 The image shows a SEM image of sample 1703 from Table 1 after roller milling.

[0135] Figure 8 This is a SEM image of the film formed from sintered sample 1A.

[0136] Figure 9 This is a SEM image of the film formed from sintered sample 1B.

[0137] Figure 10 This is a SEM image of the film formed from sintered sample 1C.

[0138] Figure 11 This is an SEM image of the spherical LTO particles produced in Example 5.

[0139] Figure 12 This is the constant current charge-discharge curve of the LTO generated in Example 5.

[0140] Figure 13 This is an SEM image of the spherical LLTO particles produced in Example 6.

[0141] Figure 14This is a magnified SEM image of the surface morphology of the spherical LLTO particles produced in Example 6. Detailed Implementation

[0142] Forming a melt

[0143] The raw materials are preferably provided in stoichiometric form of oxides. Due to the volatility of some components (such as lithium), an excess may be required to achieve the desired stoichiometric amount in the final product.

[0144] Hydroxides, hydrates, and carbonates can also be used because the gaseous reaction products are generally non-toxic. Nitrates, sulfates, and other salts are less preferred due to the formation of toxic gases and the need for a washing step to remove impurities from the garnet-like final product.

[0145] Any suitable melting vessel can be used, capable of melting the raw material to form a molten material, which can then be extracted at a controlled rate through a discharge opening, allowing the material flow to be shaped and quenched. Nozzles can be used to control the flow rate leaving the melting vessel. An electric furnace, such as an electric arc furnace, can be used. The temperature of the molten material can be determined based on the temperature required to produce the desired shaped fibers, sheets, or granules.

[0146] The melting step can be performed by heating the raw material to a melting point above the melting point of the raw material components, and to a target stoichiometric composition, on a batch, semi-batch, or continuous basis. Operation under continuous conditions requires a plug flow state to ensure minimal exposure of the raw material, thereby preventing changes in the molten material leaving the container. The furnace inlet is preferably protected from contaminant entry. Inert gases can also be used to cover the exposed melt.

[0147] Molten material can be coated in a controlled atmosphere, such as air, hydrogen, helium, or other gases, before forming and / or quenching. The purpose of controlling the atmosphere may include inhibiting chemical reactions or controlling surface tension.

[0148] Molding material formation

[0149] Generally, apart from particle formation via fluid impingement or other simultaneous quenching and forming techniques, forming processes require maintaining sufficient temperatures to allow the molten material to form the desired shape and size. Therefore, the forming step is typically carried out at a temperature similar to that of the molten material exiting the molten container (e.g., less than 200°C or less than a 100°C difference). Consequently, the forming apparatus is typically located within 1 m or 0.5 m of the molten container outlet.

[0150] fiber

[0151] A fiber is defined as having a length-to-diameter ratio of at least 3. Fibers can advantageously be produced using various techniques known in the art, including melt spinning or blow molding, to produce fibers with an arithmetic mean diameter of less than 10.0 µm, preferably less than 5.0 µm, and even more preferably less than 2.0 µm. As disclosed by the applicant in WO2017121770, ultrafine fiber diameters can be achieved using high-speed spinning techniques.

[0152] The fiber-forming temperature of molten material is similar to that of other particles formed or shaped using a rotating or spinning device.

[0153] Particles

[0154] Particles can be formed by exposing a stream of molten material to a fluid flow that simultaneously quenches and forms particles (e.g., amorphous and garnet-like crystalline materials). An average particle size of less than 2 µm can be achieved by varying the pressure and impact angle of the fluid flow. The pressure of the fluid medium can range from 1 atm to 50 atm, or from 2 atm to 20 atm, or from 3 atm to 10 atm. In some embodiments, the fluid pressure is at least 4 atm or at least 5 atm. Impact on hotter molten materials with lower viscosity can result in even lower average particle sizes, which in some embodiments can reach the submicron region.

[0155] The particles can be non-porous.

[0156] Molten material can initially form droplets before being subjected to fluid impact. Droplet formation can be achieved by those skilled in the art by adjusting the flow rate and / or outlet diameter of the molten material or by breaking up the molten material flow. A two-step particle size reduction process is beneficial for a more consistent and finer particle size distribution.

[0157] Screening and air fractionation techniques can be used to produce particles with a low average particle size (e.g., less than 1.5 µm or less than 1.0 µm).

[0158] PSDs with a D50 of about 500 nm or smaller can be manufactured, but they become more difficult to manipulate in the manufacturing process, and scaling up the manufacturing process becomes more difficult.

[0159] In some implementations, the fluid flow may be a liquid. In such implementations, the fluid flow may be sufficient to pass molten material through a nozzle and transform it into a sheet of liquid sufficient for quenching to occur.

[0160] membrane

[0161] A molten material flow can be passed between two rotating rollers to produce a thin film of molten material, which can then be passed through a quenching chamber containing a cooling medium. In one embodiment (as shown in the journal Physique; Yoshiyagawa and Tomozawa; 1982, 43, pp. C9-411-C9-414), a molten material flow is processed by two rollers to produce a thin film (< 100 µm thickness), which is then immersed in a liquid nitrogen bath to produce approximately 10 5 Cooling rate of ℃ / second.

[0162] flake crystal

[0163] WO1988008412 (incorporated herein by reference) discloses an apparatus and method for producing lamellar crystals from molten material by feeding a stream of molten material in a downward direction into a rotating cup. Details of the apparatus and operating conditions for forming lamellar crystals are provided in WO2004 / 056716, EP0289240 and US8796556, which are incorporated herein by reference.

[0164] Quenching

[0165] Before or during quenching, the molten material is preferably shaped to a sufficiently small size to achieve rapid cooling throughout the molten material, thereby generating the desired crystalline structure in the final product (e.g., the predominantly cubic crystal structure for garnet-like compositions). It should be understood that the desired size of the shaped material will depend on the cooling medium and the heat transfer properties of the shaped material (including temperature, heat capacity, and electrical conductivity). Routine experimentation may be required to optimize the quenching and material shaping processes to obtain the desired level of amorphous and targeted crystalline material. In one embodiment, the molten material preferably flows through a quenching chamber. The quenching chamber comprises: (A) A first inlet for receiving glass-ceramic material from a forming apparatus (e.g., a compressed gas injector, a rotating wheel, or a twin roller); (B) A second inlet for receiving the flow of cooling medium; and (C) An outlet for discharging quenched glass-ceramic materials from the quenching chamber.

[0166] The cooling medium can be a fluid. The fluid can be a gas or a liquid. Alternatively, the cooling medium can include a solid surface.

[0167] Quenching can be accomplished using inert gases, such as nitrogen and rare gases. Nitrogen is typically used at pressures above atmospheric pressure up to 20 bar. Helium is also used because of its greater heat capacity than nitrogen. Alternatively, argon can be used; however, its density requires significantly more energy to move, and its heat capacity is less than the alternative. The gas is preferably a compressed gas. The use of an inert gas reduces the likelihood of impurities forming during the quenching process that could affect the functionality of the final product. Air can also be used if the quality of the final product adversely affects the desired end-use application.

[0168] Alternatively, the cooling medium can be a liquid, including water or liquid nitrogen. Liquids (such as water) have the disadvantage of potentially reacting with molten material or molded articles. Additionally, further steps may be required to remove the cooling medium (such as water). In some embodiments, the process does not include water as a cooling medium and / or grinding medium.

[0169] According to various embodiments, the fluid flow can have a temperature range from about room temperature to about -200°C, from about 10°C to about -100°C, from about 0°C to about -60°C, or from about -10°C to about -50°C, including all ranges and subranges therein. The velocity range of the compressed fluid flow can be, for example, from about 0.5 ms. -1 approximately 2000 ms -1 Such as from about 1 ms -1 Approximately 1000 m s -1 From approximately 2 ms -1 approximately 100 ms -1 From approximately 5 ms -1 approximately 20 ms -1 Or from approximately 5 ms -1 approximately 15 ms -1 This includes all ranges and subranges within it. In some implementations, the fluid flow rate is at least 100 ms. -1 Or at least 150 ms -1 Or at least 200 ms -1 Or at least 250 ms -1 Or at least 300 ms -1 Or at least 350 ms -1 The fluid flow velocity can be obtained at the point of impact or at the outlet of the device that emits the fluid flow. Selecting a flow velocity suitable for the desired operation and results is within the capabilities of a person skilled in the art.

[0170] Therefore, glass-ceramics can be rapidly cooled to temperatures below their curing point, such as less than about 600°C, including temperatures such as less than about 575°C, less than about 550°C, less than about 525°C, or less than about 500°C. In some embodiments, glass-ceramics can be rapidly cooled to temperature ranges from about 200°C to about 600°C, from about 250°C to about 500°C, or from about 300°C to about 400°C, including all ranges and subranges therein.

[0171] According to various embodiments, the terms "rapid cooling," "quenching," and variations thereof are used to describe cooling a glass-ceramic to at least its curing temperature (and preferably less than 200°C or less than 150°C) within a time period sufficient to form and stabilize the desired amorphous and / or target (e.g., cubic) crystalline structure. According to various embodiments, the time period may be less than about 10 seconds, for example less than about 5.0 seconds, less than about 4.0 seconds, less than about 2.0 seconds, or less than about 1.0 seconds, but longer or shorter time periods are possible and intended to fall within the scope of this disclosure. In other embodiments, rapid cooling may occur within a time period of about 0.1 to about 0.9 seconds.

[0172] In one embodiment, the quenching process includes the step of feeding a stream of molten material into a quenching chamber, the quenching chamber comprising: An inlet used to allow the flow of molten material into the container; A means of atomizing molten material into particles by colliding it with a fluid cooling medium.

[0173] Atomization can be achieved by impinging a fluid cooling medium onto the molten material or by impinging the molten material onto the fluid cooling medium. For safety reasons, a forming agent arrangement is preferred.

[0174] In one embodiment, at least one nozzle is arranged to guide a pressure jet of fluid cooling medium to impact the molten material stream, thereby causing the molten material stream to atomize into particles.

[0175] In some embodiments, quenching and shaping of the particles are achieved by fluid impingement of a cooling fluid medium. The cooling medium may be an inert gas, such as nitrogen. Preferably, the cooling medium is cooled below ambient temperature and then recirculated into the chamber after passing through a heat exchanger (e.g., a cooler). The quenching chamber may include an inert gas under positive pressure to prevent air from entering the chamber. The quenching chamber may be positioned vertically below the molten container, where the atomized particles fall to the bottom of the container under gravity. The height of the quenching container is preferably such that the atomized particles solidify before reaching the bottom of the container.

[0176] In one implementation, the melting vessel, quenching chamber, and material transfer unit are as per GB 1340861 (which is incorporated herein by reference). Figure 1 Or configure it as disclosed in 2 (and related text).

[0177] As indicated in GB1340861, some implementation schemes may include: A flow of molten material is generated in a given volume of cooling gas. At least one fluid jet from a nozzle is guided to intersect the flow to atomize the molten material into droplets. A pressure reduction is caused by the action of a Venturi tube at or near the intersection of the jets or each jet and flow. The droplets are allowed to solidify by moving the gas through them, and the pressure reduction induces the recirculation of the gas along a cooling channel connected downstream of the intersection or each intersection to the location of the pressure reduction. The combined jets and molten material can be passed through a narrow channel to induce the Venturi action. The atomizing agent is designed to form molten vapor on several sides, such that all jets intersect each other at essentially the same point; The cooling medium is continuously cooled by circulating it through a heat exchanger. The cured particles slide or dart along the inclined cooling surface where final cooling occurs. The inclined surface reduces the risk of deformed particles interacting with it. Cooling can occur until there is no risk of particles sticking together or deforming. Cooled particles are collected at the outlet. The first fluid jet forces the molten material flow to change direction and, to some extent, breaks the melt into droplets. A second fluid jet from the nozzle then intersects the molten material flow at a distance from the point of intersection between the molten material flow and the first fluid jet, a distance that allows most of the molten material time to change direction. The second jet, substantially parallel to the initial direction of the discharge flow, completes the separation of the molten material into droplets and disperses this molten material in the chamber as a shower. A fluidized bed is used at the bottom of the quenching chamber to cool the particles; and The fluid jet and cooling gas both consist of the same inert gas.

[0178] It should be understood that in the above-mentioned quenching container, other forming devices, such as rotating cups (lamellar forming) or twin rollers (film forming), can be used to replace or supplement the pressure jet.

[0179] Example 1

[0180] A stoichiometric amount of Al₂O₃ (dopant), La₂O₃, and ZrO₂ was combined with a 20% stoichiometric excess of Li₂CO₃ to form a powder mixture, which was then added to a melt rig. A small amount of molybdenum dopant was added from a molybdenum electrode used in the melt rig. The amount of Mo added via the electrode was calculated based on the level of Mo added in previous batches operated under similar conditions.

[0181] Melting equipment ( Figure 1 The apparatus includes a cylindrical, water-cooled stainless steel container 10 with an inner diameter of 340 mm and an internal height of 160 mm. The melting device consists of two molybdenum electrodes (not shown) immersed in a powder mixture, with the electrode tips spaced approximately 5 mm apart. An alumina plate is positioned at the bottom of the apparatus, with an alumina rod covering a 14 mm orifice that serves as a discharge port.

[0182] The mixture is manually fed into container 10 through the top opening, and the generated gases are removed using an exhaust fan. The mixture is initially heated using an oxy-acetylene torch to melt a small pool, at which point the electrodes are energized to create a current between them. The power is slowly increased over 30–45 minutes, and the electrodes are further removed to build a larger molten pool in the furnace, where the temperature of the molten pool is >1250°C–1500°C. Batch process conditions are used, where the total residence time of the molten pool (once formed) does not exceed 1 hour.

[0183] Once the molten pool is large enough, the alumina rod is removed from the plate, immediately releasing the molten pool through a 14 mm orifice to form a molten flow with a material flow rate of approximately 250 kg / h. The molten flow travels approximately 500 mm in about 0.05 seconds, then is intercepted by an airflow (6 bar, approximately 7°C, approximately 0.114 m) from an air gun 20. 3 s -1 The molten material is impacted, simultaneously shaping the molten flow into particles and rapidly cooling the particles to approximately 160°C in less than one second. Therefore, the cooling rate of the molten material is at least 1000°C / second. The angle of incidence of the airflow impacting the molten flow is approximately 90°. However, this angle can vary depending on the configuration of the processing equipment (e.g., from 20° to 160°). In some embodiments, the impacted molten particles are struck vertically downwards relative to the molten container.

[0184] The air velocity emitted from the air gun is estimated to be at least 100 m / s. However, an air gun with a velocity of at least 300 m / s or at least 350 m / s may also be used.

[0185] Particulate matter travels along the quenching chamber 30 and is then collected on a stainless steel mesh in the collection box 40. No additional cooling medium is provided besides the air gun. Additional cooling can be added to the quenching chamber, including a positive inert gas flow that can run countercurrently to the molten particle flow to further increase the cooling rate, thereby increasing the amorphous content. However, in some embodiments, using a pressure jet to shape and quench the molten flow is sufficient to obtain the desired morphology.

[0186] ICP analysis results confirmed the approximate Li 5.8 Al 0.4 La3Zr 1.95 Mo 0.05 O 12 The formula.

[0187] SEM images of particles ( Figure 2 The particles are mainly spherical, ranging from approximately 1-2 µm in size or even smaller (e.g., submicron particles).

[0188] analyze Figure 2 The particle characteristics (including particle size and sphericity) of 21 samples are presented in Table A. Scandium was used. TM 5.1 Use software for data analysis.

[0189] like Figure 2 As shown, particles with diameters of approximately 2 µm, 3 µm, 4 µm, and 5 µm exist at the smaller ends of the range. However, Figure 2 Particles with diameters of approximately 20 µm, 30 µm, and 40 µm at the larger ends of the range are shown. It is anticipated that further optimization of the method will allow for the acquisition of sufficient quantities of submicron particles for separation and use in end-use applications as needed.

[0190] Table A

[0191] As can be deduced from Table A, the average maximum distance between the central axis of the particle and the nearest surface is 13.2 / 2 = 6.6 µm, and the average minimum cross-sectional size of the particle is 10.9 µm. D50 (based on the maximum diameter) is 10.2 µm.

[0192] Among the 21 samples, the maximum distance between the central axes of the particles ranged from 3.1 µm to 34.1 µm, and the sphericity ranged from 0.08 to 1.0. Sample 21 had a sphericity of 0.08. Figure 2 Elliptic-shaped particles that can be clearly identified are associated with the particles. Other particles (with a sphericity value of at least 0.63) can be considered at least quasi-spherical.

[0193] Influence of grain size on crystal / amorphous morphology

[0194] Quantitative phase analysis was performed on the size fractions of Al-doped LLZO powders with different amounts of Al dopant.

[0195] The following literature was used to perform quantitative amorphous content analysis of Rietveld: De La Torre et al. , J. Appl. Cryst ., (2001) 34 196-202; and Chapter 5 – Quantitative phase analysis in Practical Powder Diffraction Pattern Analysis using TOPAS. RE Dinnebier, A. Leinewber, JSO Evans

[0196] LaB6 was used as an internal standard for spiking. The mass of the sample and LaB6 was recorded (next slide), and the powder was mixed by hand milling for 10 minutes. The particle size used for Brindley correction during refining was 45 µm.

[0197] LaB6 MAC = 237.405 cm 2 g -1 LaB6 LAC = 1116.067 cm -1

[0198] Li7La3Zr2O 12 MAC = 205.267 cm 2 g -1 Li7La3Zr2O 12 LAC = 1040.262 cm -1

[0199] Brindley correction and LAC values ​​are applied during refinement.

[0200] The absolute weight fraction of a known material can then be calculated using the following formula:

[0201] The weight fraction of unknown or amorphous materials comes from:

[0202] As indicated in Table 1, the amount of amorphous phase increases with decreasing particle size, while the ratio of cubic to tetragonal phases remains similar. The samples in Table 1 were obtained using the method described in Example 1. Variations in dopant levels did not show a significant effect on morphology, with samples 1252 and 0981 exhibiting similar proportions of cubic and tetragonal materials, but the Al doping level in sample 0981 was twice that in sample 1252.

[0203] Table 1 Due to the high amorphous content, the minor crystalline phase is reduced (e.g., about 15 w% or less).

[0204] Comparative Examples (Samples 0960 and 1421)

[0205] Example 1 was repeated under the same conditions, but without the addition of Al2O3 dopant. XRD analysis of the resulting particles showed that a predominantly amorphous phase was still produced, but the amount of tetragonal phase was approximately twice that of the cubic phase. This highlights the effect of the dopant in stabilizing the cubic phase rather than the less ionicly conductive tetragonal phase. The results also appear to indicate that the amorphous content is independent of the particle size of the undoped LLZO sample.

[0206] Example 2: Formation of LLZO film

[0207] Ta-doped LLZO powder was produced according to the previously described method. The stoichiometric formula of the resulting powder is approximately Li. 6.5 La3Zr 1.5 Ta 0.5 O 12 Its D50 particle size is 18 µm. First, the powder is ground to a D50 particle size of 1.2 µm (i.e., the size reduction factor is 18 / 1.2 = 15).

[0208] The grinding step involves rolling LLZO particles (10:1 ZrO2:LLZO) with ZrO2 particles (10 mm diameter beads) in ethanol for 24 hours. The ground product is then calcined at the end in an anti-chamber within a glove box and stored there. There is no exposure to atmospheric H2O, thus reducing the likelihood of surface hydroxide formation. The grinding step can be eliminated by forming smaller particle sizes or by using sieving and air classification techniques to produce finer particles.

[0209] A slurry was prepared from powder, with 1% by weight of Al2O3 added as a sintering aid. The slurry was used in a casting process to form films with thicknesses ranging from 36 to 150 µm.

[0210] The membrane was heat-treated at 1320 °C for 2 minutes and then at 1200 °C for 9 hours to sinter and densify the particles. The resulting membrane had a relative density of 97%, and the total conductivity of the membrane (measured by EIS) was determined to be 0.15 mS / cm at 20 °C.

[0211] XRD pattern of powder ( Figure 4 ) and the resulting membrane ( Figure 5This indicates the transformation of Ta-LLZO powder (with 84 wt% amorphous content and also containing 9.7 wt% cubic and 7.3 wt% tetragonal garnet crystalline phases) to a Ta-LLZO film (e.g. Figure 5 The XRD pattern indicates an increase in cubic garnet crystalline phase and a significant decrease in amorphous phase.

[0212] The amorphous and crystalline phases were determined by Rietveld refinement from pXRD containing 2.5 wt% LaB6.

[0213] Example 3: Effects of amorphous content and particle size on densification and electrical conductivity.

[0214] Use with Li 6.5 La3Zr 1.5 Nb 0.5 O 12 Three Nb-doped LLZO samples (0.5Nb-LLZO) were used to prepare solid electrolyte membranes. Except as indicated, the polishing procedure (e.g., polishing beads and solvent) was performed as described in Example 2.

[0215] Sample 1632 is a sample that has been ground from a D50 size of 26.6 µm to a D50 size of 0.72 µm (size reduction factor = 36.9) using a planetary ball mill at 400 rpm for 6 x 20-minute cycles. Sample 1632 has an amorphous content of 22.4 wt%.

[0216] Sample 1703 contains unground and spherical particles with a D50 of 7.2 and an amorphous content of 85% by weight.

[0217] Sample 1703 (milled) is a sample 1703 that has been milled from a D50 size of 7.2 µm to a D50 size of 0.76 µm (size reduction factor = 9.5) using a planetary ball mill at a speed of 400 rpm for 6 x 20 minute cycles.

[0218] The particle size distribution characteristics of the samples are provided in Table 2.

[0219] Table 2

[0220] Each sample was prepared as compressed agglomerates by sintering the agglomerates in a MgO boat-shaped crucible with additives. The heating rate was increased from 20°C to 1290°C at a steep rate of 5°C / min, after which the samples were held for 7 minutes and then allowed to cool.

[0221] The relative density and conductivity of the membranes derived from the corresponding samples are provided in Table 3.

[0222] Table 3

[0223] The results show that sample 1703 (ground) has a lower relative density than sample 1632 but exhibits a 15% higher conductivity. Furthermore, the unground sample 1703 still achieves good conductivity but does not possess the optimal particle size distribution for film formation. This highlights the benefits of using particles with a high amorphous content in the formation of solid electrolytes.

[0224] Example 4 – Crystalline Size

[0225] Location X The peak shape of a diffraction peak can be understood as the convolution of several different contributions. The two most fundamental contributions are instrumental contributions. IBF(X) (Instrument Resolution Function) and sample contribution MS(X) (microstructure). Therefore, the overall peak curve of a specific reflection is described as the convolution of these two contributions. To quantitatively explain structural spectral broadening based on crystallite size, these contributions must be considered separately. IRF hkl and MS hkl Both are terms.

[0226] For measurement MS We first used standard materials with negligible structural spectral broadening to determine... IRF Then, the description was fixed when evaluating the diffraction data of sample 1A (LLZNO-20), sample 1C (LLZNO-85), and sample 1B (LLZNO-50). IRF The parameters were then used to model the broadening of other samples by refining the appropriate parameters. LaB6 powder (space group) was used. lattice parameters a = 4.155 Å) was used as the standard for determining the spectral profile. IRF Diffraction data were collected between 10 and 120 ° 2θ, with a step size of 0.016 and a time / step of 210 s. Curves were fitted using the Voigt curve function, and the peak width as a function of θ was described using the Caglioti equation, thus allowing for refinement. U, W, V Peak shapes 1 and 2. Then, refined curves and shape parameters are used to model the sample. MS This allows for the collection of diffraction data using the same optics and scanning details as those used for LaB6. The term "microcrystal" is equivalent to "homogeneous domains that produce coherent diffraction," assuming that there is no complete disruption of the three-dimensional order within them.

[0227] Table 4

[0228] The results (Table 4) show that the crystallite size decreases with changes in particle size and with increasing amorphous content. Furthermore, the crystallite growth rate (heating ramp rate of 5 °C / min from 20 °C to 1000 °C) of particles with higher amorphous content (e.g., sample 1703) is higher than that of particles with lower amorphous content (e.g., sample 1632).

[0229] Example 5 – LTO Particle Formation

[0230] Using the furnace as described in Example 1, the Li2CO3 and TiO2 precursors were prepared with a 30% molar excess of Li (i.e., Li). 5.2 Ti5O 12 Synthesis of Li4Ti5O 12 Melt blown granules. The chemical composition of the final product, determined by ICP-OES analysis, was found to contain Li. 4.1 Ti 5. Mo 0.283 O 12 The stoichiometric composition. The Mo content is derived from the molybdenum electrode in the furnace.

[0231] The melting temperature and fluid impingement conditions were similar to those described in Example 1, with PSD ranging from about 1 to 500 µm. Particles were sieved through 500, 180, and 45 µm meshes, with the majority of particles falling within the 45 to 180 µm range. Further analysis (via laser diffraction) determined that the 45–180 μm fraction had an average particle size of 81 μm and a standard deviation of 76 μm.

[0232] The relative proportions of crystalline and amorphous components in the material were assessed by Rietveld analysis using a mixture of the 45–180 μm fraction and a suitable internal standard (TiO2, 20 wt%). As indicated in Table 1, the amorphous content of sample 1777 was found to be 56 wt%. SEM images of the 45–180 μm fraction revealed that the particles were generally spherical in shape. Figure 11 ).

[0233] Electrochemical performance of LTO as an anode material

[0234] The electrochemical performance of 1 M LiPF6 dissolved in a 1:1 ethylene carbonate:dimethyl carbonate solution as the electrolyte in a lithium half-cell cell was investigated as the anode material. The LTO electrode was prepared by mixing LTO (45-180 µm fraction) with conductive carbon in a mortar at a mass ratio of 70%:30% for 20 minutes. Constant current charge-discharge curves were obtained at voltage limits of 1.5 V and 3.0 V and a controlled temperature of 20 °C. Figure 12 Achieving 152 mAh g for multiple battery cells. -1The reversible capacity is slightly lower than the expected capacity (160 mAh g). -1 Of these, the deviation is most likely to vary with electrode manufacturing.

[0235] Example 6 – LLTO Particle Formation

[0236] Using the furnace described in Example 1, Li₂CO₃, La₂O₃, and TiO₂ were synthesized from Li₂CO₃, La₂O₃, and TiO₂ with a 30% molar excess of lithium, resulting in a Li₂ with a universal composition. 3x La (2 / 3)-x Melt blow molding granules of TiO3 (0 < x < 0.16). The chemical composition of the final product was determined to be Li by ICP-OES. 0.36 La 0.54 Ti 1.01 O3. The relative proportions of crystalline and amorphous components in the material were assessed by Rietveld analysis using a mixture of 38–45 μm fractions with a suitable internal standard (TiO2, 20 wt%). As indicated in Table 1, the amorphous content was found to be 36.5 wt%. SEM images of the particles indicated that their shape was generally spherical. Figure 13 ).like Figure 14 As pointed out, the main crystalline phase can be observed through the sharp-angled morphology on the surface of spherical particles. For example... Figure 13 As noted, the morphology of the particles varies with particle size, with larger spheres (e.g., particle A) having surfaces containing sharp-angled grains, while smaller spherical particles (e.g., particle B) have smoother surfaces, consistent with particles with a higher amorphous content. Particles with a higher amorphous content can be produced by particle size separation techniques (e.g., sieving and / or air classification), or by altering production parameters (e.g., increasing the fluid impact velocity over the molten material and / or increasing the quenching rate of the atomized particles of the molten material formed during fluid impaction).

[0237] Terms and Conditions

[0238] 1. A method for producing lithium-ion conductive molded articles or precursors thereof, comprising the following steps: A. Feed the mixture of raw materials into the melting container; B. Melting the raw material in the melting vessel to form a molten material; C. Shaping the molten material; and D. Quenching the molten material with a cooling medium to produce the molded article. The cooling rate of the molten material is sufficient to form glass or glass-ceramic molded articles, and the molten material is formed before or at the same time as quenching.

[0239] 2. The method according to Clause 1, wherein the cooling medium is a fluid cooling medium.

[0240] 3. The method according to Clause 2, wherein the molten material forming and quenching by a fluid cooling medium occur simultaneously.

[0241] 4. The method according to Clause 2, wherein the molten material and the fluid cooling medium collide together, thereby atomizing the molten material into a molded article.

[0242] 5. The method according to Clause 2, wherein the molten material is quenched and shaped by impacting the fluid cooling medium onto the molten material.

[0243] 6. The method according to any one of Clauses 2 to 5, further comprising the step of feeding a molten material stream into a quenching chamber, the quenching chamber including an inlet for allowing the molten material stream to enter the container; and at least one nozzle being arranged to guide a pressure jet of a fluid cooling medium to impinge on the molten material stream, thereby causing the molten material stream to atomize into particles.

[0244] 7. The method according to any one of the preceding clauses, wherein the molten material stream impacted by the cooling medium is a plurality of molten droplets.

[0245] 8. The method according to any one of the preceding clauses, wherein the cooling medium is a gas stream, a liquid stream, or a moving object.

[0246] 9. The method according to Clause 8, wherein the gas stream is an inert gas or air.

[0247] 10. The method according to clause 8 or 9, wherein the fluid cooling medium has a cooling time of 5 ms. -1 approximately 2000 ms -1 The speed of the compressed fluid flow.

[0248] 11. The method according to any one of the preceding clauses, wherein the molten material is quenched to less than 600°C.

[0249] 12. The method according to any one of the preceding clauses, wherein the dopant is provided to the molten vessel via a sacrificial electrode.

[0250] 13. The method according to any one of the preceding clauses, wherein the molding step is performed at a temperature less than 200°C different from the temperature of the melt stream exiting the molten container.

[0251] 14. The method according to any one of the preceding clauses, wherein the molded article is a sheet, film, granules, flakes or fiber.

[0252] 15. The method according to any one of the preceding clauses, wherein the cooling rate of said molten material is sufficient to form particles comprising at least 60% by weight of an amorphous phase.

[0253] 16. The method according to any one of the preceding clauses, wherein the method produces a variety of molded articles.

[0254] 17. The method according to any one of the preceding clauses, wherein the molded article comprises a primary amorphous phase and a secondary crystalline phase.

[0255] 18. The method according to any one of the preceding clauses, wherein the molded article has an average maximum distance of less than 10 mm between the central axis of the molded article and the nearest surface, and the molded article has an average minimum cross-sectional dimension of more than 500 nm.

[0256] 19. The method according to any one of the preceding clauses, wherein the molded article has an average maximum distance of less than 250 µm between the central axis of the molded article and the nearest surface.

[0257] 20. The method according to any one of the preceding clauses, wherein the molded article has an average maximum distance of less than 100 µm between the central axis of the molded article and the nearest surface.

[0258] 21. The method according to any one of the preceding clauses, wherein the molded article has an average minimum cross-sectional dimension of more than 500 nm.

[0259] 22. The method according to any one of the preceding clauses, wherein the molded article comprises a garnet-like, perovskite-like, or spinel-like composition.

[0260] 23. The method according to any one of the preceding clauses, wherein the molded article is spherical or near-spherical.

[0261] 24. The method according to any one of the preceding clauses, wherein the molded article has a core-shell structure.

[0262] 25. The method according to any one of the preceding clauses, wherein the quenched molded article is subjected to destructive particle size reduction to reduce particle D50 by a factor of less than 100.

[0263] 26. The method according to any one of the foregoing clauses further comprises the following steps: A. The molded article is formed into a layer; B. Heat-treating the layer to densify the layer; and C. The heat treatment is carried out for a sufficient time to achieve the target morphology.

[0264] 27. The method according to any one of the preceding clauses, wherein the molded article is a spherical particle, the average maximum distance between the central axis of the particle and the nearest surface of the particle is less than 10 µm, and wherein the particle contains at least 50% by weight of an amorphous content of an amorphous phase.

[0265] 28. The method according to any one of the preceding clauses, wherein the average maximum distance between the central axis of the molded article and the nearest surface of the particle is less than 225 µm, and the average minimum cross-sectional size of the particle is greater than 600 nm.

[0266] 29. An ion-conductive glassy molded article obtained or obtainable by any of the preceding clauses.

[0267] 30. An ion-conductive glassy molded article comprising a garnet-like, perovskite-like, or spinel-like composition, wherein the average maximum distance between the central axis of the molded article and the nearest surface is less than 10 mm, and wherein the molded article comprises at least 50% by weight of an amorphous phase.

[0268] 31. The ion-conductive glassy molded article as described in any one of Clauses 29 or 30, wherein the molded article comprises at least 60% by weight of an amorphous phase.

[0269] 32. The ion-conductive glassy molded article as described in any one of clauses 29 to 31, wherein the average maximum distance between the central axis of the molded article and the nearest surface is less than 250 µm.

[0270] 33. The ion-conductive glassy molded article as described in any one of clauses 29 to 32, wherein the average maximum distance between the central axis of the molded article and the nearest surface is less than 100 µm.

[0271] 34. The ion-conductive glassy molded article as described in any one of clauses 29 to 33, wherein the average maximum distance between the central axis of the molded article and the nearest surface is not greater than 10 µm.

[0272] 35. An ion-conductive glassy molded article as described in any one of clauses 29 to 34, wherein the molded article has an average minimum cross-sectional dimension of more than 500 nm.

[0273] 36. The ion-conductive glassy molded article as described in any one of clauses 29 to 35, wherein the molded article comprises or is composed of spherical or near-spherical particles.

[0274] 37. The ion-conductive molded article according to Clause 36, wherein the spherical or near-spherical particles have an average minimum cross-sectional dimension of more than 600 nm.

[0275] 38. An ion-conductive glassy molded article according to clause 36 or 37, wherein the particles have a minimum cross-sectional size in the range of 2.4 µm to 22.9 µm.

[0276] 39. An ion-conductive glassy molded article according to any one of clauses 29 to 36, wherein the particles have a minimum cross-sectional dimension of at least 2.4 µm.

[0277] 40. The ion-conductive glassy molded article according to any one of clauses 36 to 39, wherein the particles have a particle size distribution with a D50 in the range of 600 nm to 20 µm.

[0278] 41. The ion-conductive glassy molded article according to any one of clauses 36 to 40, wherein the particles have a particle size distribution with a D50 greater than 1 µm.

[0279] 42. The ion-conductive glassy molded article according to any one of clauses 36 to 41, wherein the particles are sieved to a particle size in the range of 40 nm to 180 µm.

[0280] 43. The ion-conductive glassy molded article according to any one of clauses 29 to 42, comprising a crystalline phase with an average crystallite size of less than 690 Å.

[0281] 44. An ion-conductive glassy molded article according to any one of clauses 29 to 43, comprising at least 80% by weight of an amorphous phase.

[0282] 45. The ion-conductive glassy molded article according to any one of clauses 29 to 44, wherein the garnet-like composition comprises lithium lanthanum zirconium oxide or doped lithium lanthanum zirconium oxide.

[0283] 46. ​​The ion-conductive glassy molded article according to any one of clauses 29 to 45, wherein the perovskite-like composition comprises lithium lanthanum titanium oxide or doped lithium lanthanum titanium oxide.

[0284] 47. The ion-conductive glassy molded article according to any one of clauses 29 to 46, wherein the spinel-like composition comprises lithium titanate or doped lithium titanate.

[0285] 48. A film produced by sintering an ion-conductive glassy molded article as described in clauses 29 to 47.

[0286] 49. Use of the ion-conducting glassy molded article according to any one of clauses 29 to 47 in the manufacture of solid electrolytes or electrodes.

[0287] For the avoidance of doubt, it should be noted that in this specification, the term "comprising" in relation to compositions or particle size ranges (e.g., 40 µm to 180 µm) is considered to mean including, containing, or encompassing, and allows for the presence of other ingredients or other particle sizes. The term "comprises / comprising" should be understood in a similar manner. Many variations of the molded articles (including molded particles) of this disclosure will be apparent to those skilled in the art and are intended to be covered by this disclosure.

Claims

1. A method for producing lithium-ion conductive molded particles, the method comprising the following steps: A. Feed the mixture of raw materials into a melting vessel; B. Melting the raw material in the melting vessel to form a molten material; C. Shaping the molten material; and D. Quenching the molten material to produce the particles. The cooling rate of the molten material is sufficient to form multiple glass-ceramic particles, and the molten material is shaped before or during quenching with a fluid cooling medium; and the particles are formed by fluid impaction. The resulting ion-conductive shaped glass-ceramic particles comprise a garnet-like composition, wherein the average maximum distance between the central axis of the particle and the nearest outer surface is less than 250 µm, the average minimum cross-sectional size of the particle exceeds 500 nm, and the central axis is a central axis extending parallel to the longest 2D plane, wherein the molten material is shaped to a sufficiently small size before or during the quenching process to achieve rapid cooling throughout the molten material, thereby producing a desired level of amorphous and predominantly garnet-like cubic crystal structure.

2. The method according to claim 1, wherein the molten material is shaped while being quenched by a fluid cooling medium.

3. The method of claim 1, wherein the molten material is quenched and shaped by impacting the fluid cooling medium onto the molten material.

4. The method according to any one of claims 1 to 3, wherein the molten material is quenched to below 600°C.

5. The method according to any one of claims 1 to 3, wherein the average cooling rate is at least 400°C / second between the contact of the molten material with the fluid cooling medium and the solidification of the molten material.

6. The method according to any one of claims 1 to 3, wherein when the molten material comes into contact with the fluid cooling medium, the average temperature difference between the molten material and the cooling medium is at least 200°C.

7. The method according to any one of claims 1 to 3, further comprising the step of feeding a stream of molten material into a quenching chamber, the quenching chamber comprising: An inlet for allowing the flow of molten material into the quenching chamber; and at least one nozzle, the at least one nozzle being arranged to guide a pressure jet of fluid cooling medium to impact the molten material flow, thereby causing the molten material flow to atomize into particles.

8. The method of claim 7, wherein the chamber comprises two nozzles.

9. The method of claim 7, wherein the quenching chamber is positioned vertically below the melting vessel, and the atomized particles fall to the bottom of the quenching chamber under gravity.

10. The method of claim 9, wherein the pressure jet of the fluid cooling medium is the only fluid cooling medium used for quenching the molten material.

11. The method of claim 7, wherein the quenching chamber comprises an inert gas under positive pressure to prevent air from entering the chamber.

12. The method of claim 7, wherein the molten material stream impinged by the fluid cooling medium comprises a plurality of molten droplets.

13. The method according to any one of claims 1 to 3, wherein the cooling medium comprises a gas stream or a liquid stream.

14. The method of claim 13, wherein the gas stream is an inert gas or air.

15. The method according to any one of claims 1 to 3, wherein the fluid cooling medium has a cooling time of 0.5 ms. -1 Up to 2000 ms -1 The speed within the range.

16. The method according to any one of claims 1 to 3, wherein the fluid cooling medium has a cooling time of 5 ms -1 Up to 1000 ms -1 The speed within the range.

17. The method of claim 15, wherein the fluid cooling medium is a compressed gas.

18. The method of claim 1, wherein the glass-ceramic particles comprise at least 10% by weight of crystalline material.

19. The method according to any one of claims 1 to 3, wherein the particle has an average maximum distance of less than 100 µm between the central axis of the particle and the nearest outer surface.

20. The method according to any one of claims 1 to 3, wherein the particle has an average maximum distance of less than 50 µm between the central axis of the particle and the nearest outer surface.

21. The method according to any one of claims 1 to 3, wherein the dopant is provided to the molten vessel via a sacrificial electrode.

22. The method according to any one of claims 1 to 3, wherein the cooling rate of the molten material is sufficient to form particles comprising at least 60% by weight of an amorphous phase.

23. The method according to any one of claims 1 to 3, wherein the cooling rate of the molten material is sufficient to form particles comprising at least 80% by weight of an amorphous phase.

24. The method according to any one of claims 1 to 3, wherein the particles have a core-shell structure.

25. The method according to any one of claims 1 to 3, the method further comprising the step of separating the particles by size.

26. The method of claim 25, wherein the particles are separated by air classification or screening.

27. The method according to any one of claims 1 to 3, further comprising a washing step or a surface treatment step to remove contaminants from the particles.

28. The method of claim 7, wherein the fluid cooling medium comprises: The pressure jet of the fluid cooling medium; as well as The inert gas contained in the quenching chamber.

29. The method according to any one of claims 1 to 3, wherein the particles undergo a particle size reduction step immediately after the quenching step.

30. The method according to claim 29, wherein the quenched particles undergo a particle size reduction step to reduce particle D50 by a factor of less than 100, the size reduction factor being equal to the D50 particle size without the size reduction step divided by the D50 particle size with the size reduction step.

31. The method according to claim 29, wherein the quenched particles undergo a particle size reduction step to reduce particle D50 by a factor of less than 10, the size reduction factor being equal to the D50 particle size without the size reduction step divided by the D50 particle size with the size reduction step.

32. The method according to any one of claims 1 to 3, wherein the particles are spherical or near-spherical.

33. The method according to any one of claims 1 to 3, wherein the particles comprise at least 50% by weight of an amorphous phase.

34. Lithium-ion conductive molded particles obtained by the method according to any one of claims 1 to 33.

35. Ion-conducting glass-ceramic particles melt-formed by any one of claims 1 to 18, 21 to 28, 32 and 33, the particles comprising a garnet-like composition, wherein the average maximum distance between the central axis of the particle and the nearest outer surface is less than 250 µm, the average minimum cross-sectional size of the particle is greater than 500 nm, and the central axis is a central axis extending parallel to the longest 2D plane.

36. The ion-conducting glass-ceramic particles of claim 35, wherein the glass-ceramic particles comprise at least 10% by weight of crystalline material.

37. The ion-conductive glass-ceramic particles according to claim 35, wherein the garnet-like composition comprises lithium lanthanum zirconium oxide or doped lithium lanthanum zirconium oxide.

38. The ion-conducting glass-ceramic particles according to any one of claims 35 to 37, comprising at least 80% by weight of an amorphous phase.

39. The ion-conductive glass-ceramic particles according to any one of claims 35 to 37, wherein the average maximum distance between the central axis of the particles and the nearest outer surface is less than 100 µm.

40. The ion-conductive glass-ceramic particles according to any one of claims 35 to 37, wherein the average maximum distance between the central axis of the particles and the nearest outer surface is not greater than 10 µm.

41. The ion-conductive glass-ceramic particles according to any one of claims 35 to 37, wherein the particles have a minimum cross-sectional dimension of at least 2.40 µm.

42. The ion-conductive glass-ceramic particles according to any one of claims 35 to 37, wherein the particles have a minimum cross-sectional size in the range of 2.4 µm to 22.9 µm.

43. The ion-conductive glass-ceramic particles according to any one of claims 35 to 37, wherein the particles have a particle size distribution with a D50 in the range of 600 nm to 20 µm.

44. The ion-conducting glass-ceramic particles according to any one of claims 35 to 37, wherein the particles have a particle size distribution with a D50 greater than 1 µm.

45. The ion-conductive glass-ceramic particles according to any one of claims 35 to 37, wherein the particles comprise a sieve particle size in the range of 40 µm to 180 µm.

46. ​​The ion-conductive glass-ceramic particles according to any one of claims 35 to 37, wherein the particles have a core-shell structure.

47. The ion-conducting glass-ceramic particles according to any one of claims 35 to 37, wherein the particle size D50 is in the range of 600 nm to 20 µm; and the sphericity is 0.7 or greater.

48. A composite material comprising a solvent-soluble inorganic binder matrix, wherein the solvent-soluble inorganic binder matrix comprises: Solvent-soluble inorganic adhesives; as well as Multiple ion-conducting glass-ceramic particles as described in any one of claims 35 to 47; The amount of the ionicly conductive particles is in the range of 20% to 99.5% by weight, based on the total weight of the ionicly conductive particles and the solvent-soluble inorganic binder.

49. A method for forming a membrane, the method comprising the steps of: A. An ion-conducting glass-ceramic particle layer is formed, the ion-conducting glass-ceramic particle comprising a garnet-like composition, wherein the average maximum distance between the central axis of the particle and the nearest outer surface is less than 250 µm, the average minimum cross-sectional size of the particle is greater than 500 nm, the particle is spherical or quasi-spherical and comprises at least 50 wt% of an amorphous phase and a predominantly garnet-like cubic crystal structure, and the central axis is a central axis extending parallel to the longest 2D plane; B. Heat-treating the layer to densify the layer; and C. The heat treatment is carried out for a sufficient time to achieve the target morphology.

50. The method of claim 49, wherein the densified layer has a density of at least 97%.

51. The method of claim 49, wherein the densification transforms predominantly amorphous particles into a predominantly crystalline film.

52. A membrane produced by the method according to any one of claims 49 to 51, wherein the thickness of the membrane is between 5 µm and 500 µm.

53. A membrane produced by the method according to any one of claims 49 to 51, wherein the ion-conductive glass-ceramic particles comprise a garnet-like composition, wherein the particle size D50 is in the range of 600 nm to 20 µm; the sphericity is 0.7 or greater; and the particles comprise at least 50% by weight of an amorphous phase.

54. Use of the ion-conducting glass-ceramic particles according to any one of claims 35 to 47 in the manufacture of solid electrolytes or electrodes.

Citation Information

Patent Citations

  • Method and apparatus for glass flakes

    EP0289240A1

  • Method of and apparatus for producing a particulate material

    GB1340861A

  • Synthesis of nanosized cubic lithium lanthanum zirconate fast ion conductor

    US20190062176A1

  • Lithium-ion-conducting composite material and process for producing

    US20190173130A1

  • Process for producing spherical glass particles

    US4781741A